DINAMIKA HUBUNGAN ANTARA KOREA UTARA DAN KOREA SELATAN TAHUN 2018-2019 - Yesica Olivia; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Korean Peninsula finally achieved a significant improvement in their diplomatic relations in 2018 after North Korea opened its diplomatic relation for South Korea and United States of America. However, towards the end of 2019, diplomatic relations on Korean Peninsula deteriorated again. In order to understand why this dynamic happen, this research used Copenhagen School as its perspective and Regional Security Complex as its theory. Through this perspective, the security concept is reconstructed in a way that security isn’t always about the military but includes economy, politics, society and environment. With the reconstruction, a full of competition, suspicion, balance of power and alliances interdependency that influenced by a country from outside the region was formed. By using the library research method, this research will explain the relations between North Korea, South Korea and United States of America and how the United States of America’s intervention played a role in the continuation of Korean Peninsula diplomatic relations. Keywords: Panmunjeom Declaration, Cooperation, Denuclearization